Penggunaan Media Pembelajaran Daring dalam Proses Perkuliahan Mahasiswa Pendidikan Matematika FKIP Universitas Batanghari Tahun Akademik 2021/2022 - Ayu Yarmayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In online learning, the existence of a class where learning is held is replaced by a virtual class called a learning management system (LMS). In online learning, systematic learning design needs to be done. The goal is to produce a semester learning plan (RPS) along with learning tools, such as assessment instruments and learning objects that are efficient and effective. The research method used in this research is using qualitative research methods. Qualitative research methods are often called naturalistic research methods because the research is carried out in natural conditions. This shows that the implementation of this research does occur naturally, as it is, in normal situations that are not manipulated by circumstances and conditions emphasize descriptions naturally. Research subjects are students in courses taught by researchers in certain semesters. The research subject selection technique used is the Purposive Sampling Technique. Online learning media used during learning include whatsapp group, google classroom, zoom and google meeting. 50% of online learning media used by lecturers is google classroom, while 41.7% of students prefer online learning media through zoom meetings. The zoom application is the student's choice because it is very helpful in understanding the material in mathematics learning. Some of the obstacles during online learning include the internet network, difficulty understanding the material and being easily bored. The obstacles experienced by students during online learning are 75% due to the internet network, 16.7% have difficulty understanding the material and 8.3% are easily bored. The frequency of giving assignments by lecturers during online learning is in the manycategory, which is 91.7%. Students' feelings about online learning amounted to 83.3% stated that they were not happy.